Disability as a Social Construction: Investigating How Autism is Represented in the Mainstream Media - Hamilton, Lauren (PRISM: Casting New Light on Learning, Theory and Practice, 2019)
This paper employs Critical Discourse Analysis to examine the representation of autism within a small sample of mainstream newspaper articles. The paper concludes that media, as a communicative tool, has enormous cultural power whereby the portrayal of Autism as a disability is predicated on notions of normality and underpinned by ableist ideology. Such promotion of normalcy and disability in general can serve to generate and sustain disabling barriers and oppression. This hegemonic practice therefore produces a replicative process that is detrimental to the production of social justice and equality within contemporary society and culture.